Prognostic Value of the Sum of Metabolic Tumor Volume of Primary Tumor and Lymph Nodes Using 18F-FDG PET/CT in Patients With Cervical Cancer. Issue 9 (March 2016) - Hong, Jin Hwa; Min, Kyung Jin; Lee, Jae Kwan; So, Kyeong A; Jung, Un Suk; Kim, Sungeun; Eo, Jae Seon
Abstract : Abstract: This is an observational study to determine the most relevant parameter of 18 F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) for predicting recurrence in cervical cancer. Fifty-six patients with International Federation of Gynecology and Obstetrics (FIGO) stage IIB-IVA cervical cancer who underwent pretreatment 18 F-FDG PET/CT were enrolled. PET parameters including maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) of both primary tumor and pelvic and/or para-aortic lymph nodes were analyzed. SUVmax-S was defined as the sum of the SUVmax of primary tumor and the higher SUVmax of either pelvic or para-aortic lymph nodes. MTV-S was defined as the sum of the MTV of primary tumor and pelvic and para-aortic lymph nodes. TLG-S was calculated in the same way as MTV-S. We evaluated the relationship between these PET parameters and recurrence-free survival (RFS). Univariate analysis revealed that higher FIGO stage (hazard ratio [HR] = 5.61, 95% confidence interval [CI]: 1.68–18.68, P = 0.005), lymph node metastasis (HR = 3.42, 95% CI: 1.08–10.84, P = 0.037), MTV of primary tumor >47.81 cm 3 (HR = 6.20, 95% CI: 1.35–28.48, P = 0.019), TLG of primary tumor >215.02 (HR = 11.82, 95% CI: 1.52–91.96, P = 0.018), MTV-S > 59.01 cm 3 (HR = 8.24, 95% CI: 1.80–37.77, P = 0.007), and TLG-S > 224.15 (HR = 13.09, 95% CI: 1.68–101.89, P = 0.014) were associated with RFS. In multivariate analysis, FIGO stage (HR = 4.87, 95% CI: 1.38–17.18, P = 0.014) and MTV-S > 59.01 cm 3 (HR = 7.37, 95% CI: 1.54–35.16, P = 0.012) were determined to be independent predictive factors for RFS. Our preliminary results reveal that MTV-S is an independent prognostic factor for RFS in patients with cervical cancer treated by definitive chemoradiotherapy.